Hey!!
15. Find the area of the quadrilateral whose vertices, taken in order, are (– 4, – 2), (– 3, – 5), (3, – 2) and ( 2 , 3)
Standard:- 10
❎Don't Spamming❎
Thanks ☺☺
Answers
Answered by
5
Let the vertices of the Quadrilateral are:
A(-4,-2), B(-3,-5), C(3,-2) and D(2,3).
Area of triangle ABD:
Here,
x1 = -4, x2 = -2.
x2 = -3, y2 = -5
x3 = 2, y3 = 3.
![= \ \textgreater \ \frac{1}{2} (x1(y2 - y3) + x2(y3 - y1) + x3(y1 - y2)) = \ \textgreater \ \frac{1}{2} (x1(y2 - y3) + x2(y3 - y1) + x3(y1 - y2))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%28x1%28y2+-+y3%29+%2B+x2%28y3+-+y1%29+%2B+x3%28y1+-+y2%29%29)
![= \ \textgreater \ \frac{1}{2} (-4(-5 - 3) + (-3)(3 - (-2)) + 2(-2 - (-5)) = \ \textgreater \ \frac{1}{2} (-4(-5 - 3) + (-3)(3 - (-2)) + 2(-2 - (-5))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%28-4%28-5+-+3%29+%2B+%28-3%29%283+-+%28-2%29%29+%2B+2%28-2+-+%28-5%29%29)
![= \ \textgreater \ \frac{1}{2} (-4(-8) + (-3)(5) + 2(3)) = \ \textgreater \ \frac{1}{2} (-4(-8) + (-3)(5) + 2(3))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%28-4%28-8%29+%2B+%28-3%29%285%29+%2B+2%283%29%29)
![= \ \textgreater \ \frac{1}{2}(32 - 15 + 6) = \ \textgreater \ \frac{1}{2}(32 - 15 + 6)](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D%2832+-+15+%2B+6%29+)
![= \ \textgreater \ \frac{1}{2} (23) = \ \textgreater \ \frac{1}{2} (23)](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%2823%29)
![= \ \textgreater \ 11.5 = \ \textgreater \ 11.5](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+11.5)
Area of Triangle BCD:
Here,
x1 = -3, y1 = -5
x2 = 3, y2 = -2
x3 = 2, y3 = 3
![= \ \textgreater \ \frac{1}{2}(x1(y2 - y3) + x2(y2 - y3) + x3(y1 - y2)) = \ \textgreater \ \frac{1}{2}(x1(y2 - y3) + x2(y2 - y3) + x3(y1 - y2))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D%28x1%28y2+-+y3%29+%2B+x2%28y2+-+y3%29+%2B+x3%28y1+-+y2%29%29)
![= \ \textgreater \ \frac{1}{2}(-3(-2 - 3) + 3(3 - (-5)) + 2(-5 - (-2)) = \ \textgreater \ \frac{1}{2}(-3(-2 - 3) + 3(3 - (-5)) + 2(-5 - (-2))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D%28-3%28-2+-+3%29+%2B+3%283+-+%28-5%29%29+%2B+2%28-5+-+%28-2%29%29+)
![= \ \textgreater \ \frac{1}{2} ( -3(-5) + 3(8) + 2(-3)) = \ \textgreater \ \frac{1}{2} ( -3(-5) + 3(8) + 2(-3))](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%28+-3%28-5%29+%2B+3%288%29+%2B+2%28-3%29%29)
![= \ \textgreater \ \frac{1}{2} (15 + 24 - 6) = \ \textgreater \ \frac{1}{2} (15 + 24 - 6)](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D+%2815+%2B+24+-+6%29)
![= \ \textgreater \ \frac{1}{2}(33) = \ \textgreater \ \frac{1}{2}(33)](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+%5Cfrac%7B1%7D%7B2%7D%2833%29+)
![= \ \textgreater \ 16.5 = \ \textgreater \ 16.5](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C+16.5)
Therefore:
Area of Quadrilateral ABCD = Area of Triangle ABD + Area of triangle BCD
= 11.5 + 16.5
= 28 square units.
Hope this helps!
A(-4,-2), B(-3,-5), C(3,-2) and D(2,3).
Area of triangle ABD:
Here,
x1 = -4, x2 = -2.
x2 = -3, y2 = -5
x3 = 2, y3 = 3.
Area of Triangle BCD:
Here,
x1 = -3, y1 = -5
x2 = 3, y2 = -2
x3 = 2, y3 = 3
Therefore:
Area of Quadrilateral ABCD = Area of Triangle ABD + Area of triangle BCD
= 11.5 + 16.5
= 28 square units.
Hope this helps!
siddhartharao77:
:-)
Similar questions